Hepatotoxicity, Nephrotoxicity and Oxidative Stress in Rat Testis Following Exposure to Haloxyfop-p-methyl Ester, an Aryloxyphenoxypropionate Herbicide - Ebenezer Tunde Olayinka; Ayokanmi Ore (Toxics, 2015)
Haloxyfop-p-methyl ester (HPME) ((R)-2-{4-[3-chloro-5-(trifluoromethyl)-2-pyridyloxy]phenoxy}propionic acid), is a selective aryloxyphenoxypropionate (AOPP) herbicide. It exerts phytotoxicity through inhibition of lipid metabolism and induction of oxidative stress in susceptible plants. This study investigated the toxicological potentials of HPME in rats. Twenty-four male Wistar rats (170–210 g) were randomized into four groups (I–IV). Group I (control) received 1 mL of distilled water, while animals in Groups II, III and IV received 6.75, 13.5 and 27 mg/kg body weight HPME, respectively, for 21 days. There was a significant (p < 0.05) increase in renal and hepatic function biomarkers (urea, creatinine, total bilirubin, ALP, ALT, AST) in the plasma of treated animals compared to control. Levels of testicular antioxidants, ascorbic acid and glutathione, and activities of glutathione-S-transferase, superoxide dismutase and catalase were reduced significantly after 21 days of HPME administration in a dose-dependent manner. The testicular malondialdehyde level increased significantly in the HPME-treated rats relative to the control. A significant decrease in testicular lactate dehydrogenase, acid phosphatase and γ-glutamyl transferase was also observed in HPME-treated animals. Testicular histology revealed severe interstitial edema and sections of seminiferous tubules with necrotic and eroded germinal epithelium in the HPME-treated rats. Overall, data from this study suggest that HPME altered hepatic and renal function and induced oxidative stress and morphological changes in the testis of rats.